Phytochemical analysis and biological effects of Zingiber cassumunar extract and three phenylbutenoids: targeting NF-κB, Akt/MAPK, and caspase-3 pathways - Thidaporn Gundom; Wanida Sukketsiri; Pharkphoom Panichayupakaranant (BMC Complementary Medicine and Therapies)
Abstract Background Zingiber cassumunar Roxb., belonging to the Zingiberaceae family, is a medicinal herb commonly found in tropical regions, particularly in Southeast Asia. This research aims to investigate the preventive effects and anti-inflammatory properties of a phenylbutenoid extract (PE) obtained from the rhizomes of Z. cassumunar. Method The PE extract was prepared using green microwave extraction and subsequently analyzed by high-performance liquid chromatography. To evaluate its anti-inflammatory activity, lipopolysaccharide (LPS)-stimulated RAW264.7 cell models were used to measure the release of nitric oxide (NO), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) using the Griess assay and enzyme-linked immunosorbent assay, respectively. Additionally, the inhibitory effects of PE on apoptosis and reactive oxygen species (ROS) production were evaluated in hydrogen peroxide-induced C2C12 myoblast cells. The expression of inflammation- and apoptosis-related proteins was evaluated using western blotting. Results The results indicated that the PE was enriched with (E)-(3,4-dimethoxyphenyl)butadiene (DMPBD), (E)-1-(3,4-dimethoxyphenyl)but-3-en-1-ol (compound D), and (E)-1-(3,4-dimethoxyphenyl)but-3-en-1-yl acetate (compound D acetate). The PE contained a total phenylbutenoid content of 1.42% w/w. The PE exhibited potent anti-inflammatory properties, with half maximal inhibitory concentration (IC50) values of 7.2 µg/mL for NO, 23.4 µg/mL for TNF-α, and 19.8 µg/mL for IL-1β. In comparison, DMPBD exhibited lower activity against NO and TNF-α (IC50 values of 16.3 and 37.2 µg/mL, respectively) but similar efficacy against IL-1β (IC50 of 17.7 µg/mL) in LPS-induced RAW264.7 cells. All test compounds significantly decreased the percentage of apoptotic cells and suppressed intracellular ROS production in hydrogen peroxide-induced C2C12 myoblast cells. Notably, PE exhibited the highest potency in reducing apoptotic cells, with the lowest IC50 value of 11.6 µg/mL. PE inhibited the expression of p-p38/p38, pERK/ERK, and pAkt/Akt in the LPS-induced inflammatory response in RAW264.7 cells. Additionally, PE significantly suppressed the cleaved/pro-caspase-3 ratio without affecting Bax and Bcl-2 protein levels. Conclusion These findings suggest that PE and its phenylbutenoids exhibit anti-inflammatory effects through the inhibition of p38, ERK, and Akt signaling pathways, and anti-apoptotic effects via the inhibition of the caspase-3 pathway, highlighting their therapeutic potential for managing inflammatory and degenerative conditions. Clinical trial number Not applicable.